The Influence of Character Education on Student's Self-Concept - Repelita, Rudi; Atikah, Cucu (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze whether there is an influence of character education on the self-concept of students at SMA Negeri 1 Kota Serang. The method used is correlational survey with simple random sampling technique. The research sample involved 100 students from SMA Negeri 1 Kota Serang. Hypothesis testing was conducted using linear regression analysis, and the results showed that character education affects the formation of students' self-concept. Based on these findings, it is recommended that teachers increasingly integrate character education values in the classroom learning process to help students build a positive self-concept.